2020
DOI: 10.1007/s00427-020-00654-9
|View full text |Cite
|
Sign up to set email alerts
|

six3 acts upstream of foxQ2 in labrum and neural development in the spider Parasteatoda tepidariorum

Abstract: Anterior patterning in animals is based on a gene regulatory network, which comprises highly conserved transcription factors like six3, pax6 and otx. More recently, foxQ2 was found to be an ancestral component of this network but its regulatory interactions showed evolutionary differences. In most animals, foxQ2 is a downstream target of six3 and knockdown leads to mild or no epidermal phenotypes. In contrast, in the red flour beetle Tribolium castaneum, foxQ2 gained a more prominent role in patterning leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…Arachnida have shown that Arachnopulmonata ( segment defects, but no eye patterning defects were reported by the authors (Turetzek et al, 140 2015). More recently, a functional interrogation of Ptep-Six3 paralogs, focused on labrum 141 development, reported no discernible morphological phenotype, despite a lower hatching rate 142 than controls and disruption of a downstream target with a labral expression domain 143 (Schacht, Schomburg, & Bucher, 2020 As first steps toward these goals, we first developed transcriptomic resources for a sister 162 species pair of cave-dwelling Charinus whip spiders, wherein one species exhibits typical eye 163 morphology and the other highly reduced eyes (a troglobitic condition). We applied a 164 differential gene expression (DGE) analysis to these datasets to investigate whether candidate 165 RDGN genes with known expression patterns in model spider species (C. salei, P. 166 tepidariorum) exhibit differential expression in non-spider arachnopulmonates, as a function 167 of both eye condition and developmental stage.…”
mentioning
confidence: 99%
“…Arachnida have shown that Arachnopulmonata ( segment defects, but no eye patterning defects were reported by the authors (Turetzek et al, 140 2015). More recently, a functional interrogation of Ptep-Six3 paralogs, focused on labrum 141 development, reported no discernible morphological phenotype, despite a lower hatching rate 142 than controls and disruption of a downstream target with a labral expression domain 143 (Schacht, Schomburg, & Bucher, 2020 As first steps toward these goals, we first developed transcriptomic resources for a sister 162 species pair of cave-dwelling Charinus whip spiders, wherein one species exhibits typical eye 163 morphology and the other highly reduced eyes (a troglobitic condition). We applied a 164 differential gene expression (DGE) analysis to these datasets to investigate whether candidate 165 RDGN genes with known expression patterns in model spider species (C. salei, P. 166 tepidariorum) exhibit differential expression in non-spider arachnopulmonates, as a function 167 of both eye condition and developmental stage.…”
mentioning
confidence: 99%
“…In the light of the topological congruence and corresponding developmental sequence in the two median eye pairs of xiphosurans and the basally branching pycnogonids, a promising future research avenue would be the study of anterior head patterning genes and the retinal determination gene network known to govern arthropod eye differentiation. To date, such studies are still rare in chelicerates and almost exclusively confined to spiders (e.g., [ 118 , 119 ]; but see [ 120 ]), revealing differential gene expression patterns during the development of their different eye types [ 121 , 122 ]. Accordingly, equivalent studies on the development of the two median eye pairs in pycnogonids and xiphosurans versus the single median eye pair of terrestrial euchelicerate taxa have the potential to uncover further eye type-specific similarities/discrepancies between the lineages and thus yield novel developmental data impacting current views on the evolution of the visual system in Chelicerata.…”
Section: Discussionmentioning
confidence: 99%
“…RDN gene expression in P. tepadariorum and C. salei shows varying combinations in primary and secondary eyes. Expression is also inconsistent across species (Schomburg et al, 2015;Samadi et al, 2015;Turetzek et al, 2016;Schacht et al, 2020) (Fig. 6C).…”
Section: Arachnidsmentioning
confidence: 99%
“…These patterns might be evidence of neofunctionalization or subfunctionalization of these duplicated genes in the developing visual system. Current functional investigations suggest that six3 paralogs are redundant in P. tepidariorum but that soA/Pt-so1 is necessary for the development of both primary and secondary eyes (Schacht et al, 2020;Gainett et al, 2020 preprint) The evolution of complex non-cephalic visual systems and the role of developmental constraint…”
Section: Arachnidsmentioning
confidence: 99%